Comparative evaluation of average doses of radiation of population of Irkutsk and Voronezh regions according to «Unified state system of control of individual doses» - V. N. Rakitsky; M. K. Kuzmichev; O. V. Klepikov; G. V. Kurenkova (Радиационная гигиена)
The aim of the study was a comparative assessment of radiation doses to the population of the Voronezh and Irkutsk regions according to the unified state system for monitoring individual doses and radiation-hygienic certification. The objects of research were the territories of the Voronezh and Irkutsk regions, significantly differing in climatic conditions and resources, industrial potential, but comparable in terms of population. The subject of the study was the average territorial values of radiation doses to personnel due to the normal operation of anthropogenic sources, radiation doses to the population due to natural sources and anthropogenic background, radiation doses to patients due to the use of ionizing radiation in medical diagnostics. The method of comparative analysis of effective collective and individual average annual radiation doses was used. In the Voronezh and Irkutsk regions, the priority dose-generating factor is natural radiation, which contribution to the annual effective collective dose is 83.33 and 89.18%, respectively. At the same time, the average individual annual effective doses to the population due to natural sources of ionizing radiation in the Irkutsk region in relation to the Voronezh region are significantly higher for radon – 2,81 times, due to the content of radionuclides in drinking water – 1,93 times and external terrigenous radiation – 1,46 times, which leads to a two-fold difference in the total individual effective doses associated with natural sources of ionizing radiation. These differences are explained by the features of the physical and geographical location of territories. There are significant differences in the values of the average effective annual doses of the population due to global fallouts and past radiation accidents, because a part of the territory of the Voronezh region was exposed to radioactive contamination as a result of the accident at the Chernobyl nuclear power plant (in the Voronezh region – 0.062 mSv / year, in the Irkutsk -0.005 mSv / year). Radiography (63.15 and 67.27%) makes the leading contribution to the value of medical radiation doses, which occupy the second place in the structures of the effective collective annual doses to the population (in the Voronezh region make up 16.46%, in the Irkutsk region – 10.74%) and fluorography (31.29 and 27.41% in the regions, respectively). It was established that the radiation situation in the Voronezh and Irkutsk regions remains stable and safe.